Effect of Pawpaw (Carica papaya) seed meal on the reproductive, endocrine and immune system of Mozambique tilapia (Oreochromis mossambicus) - Omeje, Victor Okonkwo (Stellenbosch : Stellenbosch University, 2016)
Thesis (PhD)--Stellenbosch University, 2016.